Intimate Enemies : Violence and Reconciliation in Peru - Theidon, Kimberly Susan (Book collections on Project MUSE., 2013)
In the aftermath of a civil war, former enemies are left living side by side-and often the enemy is a son-in-law, a godfather, an old schoolmate, or the community that lies just across the valley. Though the internal conflict in Peru at the end of the twentieth century was incited and organized by insurgent Senderistas, the violence and destruction were carried out not only by Peruvian armed forces but also by civilians. In the wake of war, any given Peruvian community may consist of ex-Senderistas, current sympathizers, widows, orphans, army veterans-a volatile social landscape. These survivors, though fully aware of the potential danger posed by their neighbors, must nonetheless endeavor to live and labor alongside their intimate enemies. Drawing on years of research with communities in the highlands of Ayacucho, Kimberly Theidon explores how Peruvians are rebuilding both individual lives and collective existence following twenty years of armed conflict. Intimate Enemies recounts the stories and dialogues of Peruvian peasants and Theidon's own experiences to encompass the broad and varied range of conciliatory practices: customary law before and after the war, the practice of arrepentimiento (publicly confessing one's actions and requesting pardon from one's peers), a differentiation between forgiveness and reconciliation, and the importance of storytelling to make sense of the past and recreate moral order. The micropolitics of reconciliation in these communities present an example of postwar coexistence that deeply complicates the way we understand transitional justice, moral sensibilities, and social life in the aftermath of war. Any effort to understand postconflict reconstruction must be attuned to devastation as well as to human tenacity for life.